2014
DOI: 10.1080/10255842.2013.843675
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis ofpectus carinatumsurgical correction via a minimally invasive approach

Abstract: Pectus carinatum (PC) is a chest deformity caused by a disproportionate growth of the costal cartilages compared to the bony thoracic skeleton, pulling the sternum towards, which leads to its protrusion. There has been a growing interest on using the 'reversed Nuss' technique as a minimally invasive procedure for PC surgical correction. A corrective bar is introduced between the skin and the thoracic cage and positioned on top of the sternum highest protrusion area for continuous pressure. Then, it is fixed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…One study was identified by backward citation. Eventually, 48 studies were included: 19 in category I [ 5 , 9 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], 21 in category II [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , and 8 in category III [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ( Figure 1 ).
Figure 1 PRISMA 2020 flow diagram of identification, screening, and inclusion of papers in the 3 categories.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was identified by backward citation. Eventually, 48 studies were included: 19 in category I [ 5 , 9 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], 21 in category II [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , and 8 in category III [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ( Figure 1 ).
Figure 1 PRISMA 2020 flow diagram of identification, screening, and inclusion of papers in the 3 categories.
…”
Section: Resultsmentioning
confidence: 99%
“…Five studies focused on the change of thoracic pressure distribution after PD correction [ 25 , 58 , [60] , [61] , [62] ]. CT models correctly predicted surgical outcome [ 25 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The virtual bar was created in a computer-aided design software, i.e. Solidworks, (SolidWorks Corp., Concord, MA, USA) 33 . The material properties of titanium alloy Ti-6Al-4V were considered for the bar 34 .…”
Section: Generation Of the Patient-specific Biomechanical Modelmentioning
confidence: 99%
“…CLINICAL CASES ковом возрасте [4,5,6,7]. Использование известных современных малоинвазивных технологий лечения деформаций грудной клетки при данном пороке значимого клинического эффекта не дает [8][9][10][11].…”
unclassified